Digital Transformation of Refillable Water Services Using the Easy Galon Android-Based System - Rahmah, Ummiati; Mustapa, Mahmud; Budiarti, Nur Azizah Eka (PT. Lontara Digitech Indonesia, 2025)
The advancement of technology in this period has been exceedingly swift. The plethora of emerging innovations compels individuals to remain current. The selling of gallons constitutes a significant and prevalent industry, prompting numerous gallon enterprises to transition to an online sales model via mobile applications. Consequently, the researchers choose to develop an innovative and user-centric Gallon Refill Water Sales Application. This article elucidates how the Gallon Refill Water Sales Application has enhanced efficiency and ease in the purchasing process. This program enables consumers to swiftly and effortlessly order gallons via their mobile devices. Users can see the inventory of available products, preferred brands, and execute payments using the COD (Cash On Delivery) method